Who Did What to Whom?: Anaphoric Subjects and Objects in Daniel 11:2b–12:3 - Li, Tarsee (Bulletin for biblical research, 2024)
The numerous anaphoric references in the prophetic narrative of Dan 11:2b-12:3, including some ambiguous ones, offer us a good test case for the rules proposed by Lénart J. de Regt for dealing with ambiguity in anaphoric references in biblical Hebrew narrative. This article concludes that the rules provide a useful tool for clarifying some of the ambiguous anaphors in the passage.